Development of Canva-Based LowkE-Book Learning Media as a Companion to PjBL to Improve Student Learning Outcomes - Izza Nafisah Fikriyyani; Teguh Supriyanto; Trimurtini (Jurnal Penelitian Pendidikan IPA, 2024)
This research uses research and development methods which refer to the Borg and Gall model. This research was conducted with the aim of developing and testing the feasibility, practicality and effectiveness of Canva-based LowkE-Book learning media. This research involved 27 students with 6 small-scale trial subjects and 21 large-scale trial subjects at SD Negeri Sadeng 01. The data collection technique used was a test technique (pretest-posttest) and non-test in the form of observation results, questionnaires, interview results and document data. The validation results carried out by media expert validators and material experts showed that the Canva-based LowkE-Book learning media had met the valid criteria with a score of 90% by the media expert validator, and 96% by the material expert validator. Based on the pretest-posttest results, it is known that the Canva-based LowkE-Book is effective in improving student learning outcomes as evidenced by the increase in the average pretest score from 42.85 to 85.14 at the time of the posttest and the n gain test results obtained <g> value gain of 0.74 in the high category. Based on the results of the response questionnaire distributed, very positive responses were obtained from teachers and students. Based on these results, it can be concluded that the Canva-based LowkE-Book learning media is effective for improving learning outcomes in science subjects and is feasible and practical to apply in student learning.